How does climate change alter agricultural strategies to support food security? Background paper for the conference "Food Security Futures: Research Priorities for the 21st Century" held in Dublin, Ireland, 11-12 April 2013 - Thornton, Philip K.; Lipper, Leslie; Baas, S.; Cattaneo, Andrea; Chesterman, Sabrina; Cochrane, K.; Young, C. de; Ericksen, Polly J.; Etten, Jacob van; Clerck, F. de; Douthwaite, Boru; DuVal A; et al. (2013)
In this paper we focus on the issue of how climate change affects the way that agricultural systems and the people that manage and govern them need to change in the next 20 years in order to achieve food security, and how FAO and CGIAR can support that change. We build on a huge body of literature on sustainable agricultural development and intensification, as well as work on nutrition security and resource use efficiency, much of which is articulated in other papers in this conference.